1992
DOI: 10.1104/pp.100.1.334
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Two Superoxide Dismutase Isozymes and Their Subcellular Localization in Needles and Roots of Norway Spruce (Picea abies L.) Trees

Abstract: Two isozymes of superoxide dismutase (SOD; EC 1.15.1.1) were purified from Norway spruce (Picea abies L.) needles to apparent electrophoretic homogeneity. Purification factors were 354 for SOD I and 265 for SOD II. The native molecular mass of both purified enzymes was approximately 33 kD, as determined by gel filtration. The subunit molecular weights, as estimated by sodium dodecyl sulfate polyacrylamide gel electrophoresis, were 20,000 for SOD I and 16,000 for SOD II in the presence of 2-mercaptoethanol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Two bands of each accession were more towards cathodic side, possibly having net positive charge and high molecular weight, while rest bands were towards anode indicating net negative charge and corresponding low molecular weights. The number of isozymes of SOD had been reported to vary, viz., 2 in roots and needles of Picea abies (Kroniger et al 1992), 3 in Spirulina (Lumsden and Hall 1974), kidney bean leaves (Kono et al 1979), Brussels sprouts (Walker et al 1991) and Fagopyrum tataricum cv. Wutai leaves (Wang et al 1993), 4 in maize (Gianopolitis and Ries 1977) and tomato (Kumar et al 2006) and 5 in maize (Baum et al 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Two bands of each accession were more towards cathodic side, possibly having net positive charge and high molecular weight, while rest bands were towards anode indicating net negative charge and corresponding low molecular weights. The number of isozymes of SOD had been reported to vary, viz., 2 in roots and needles of Picea abies (Kroniger et al 1992), 3 in Spirulina (Lumsden and Hall 1974), kidney bean leaves (Kono et al 1979), Brussels sprouts (Walker et al 1991) and Fagopyrum tataricum cv. Wutai leaves (Wang et al 1993), 4 in maize (Gianopolitis and Ries 1977) and tomato (Kumar et al 2006) and 5 in maize (Baum et al 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies suggested that environmental factors, such as light, temperature, or even airborne photooxidants to be the forces causing seasonal antioxidants fluctuations. Kroniger et al (1992) suggested that the seasonal variation in antioxidants to be developmentally controlled. In our study, antioxidant enzyme activities decreased as air temperature increased, but increased when temperature dropped, indicating that temperature was involved in the changes in the antioxidant system for creeping bentgrass.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase activity was determined by the inhibition of the formation of epinephrine at pH 10.4 and 30°C (Kroniger et al 1992). One unit of superoxide dismutase activity was defined as the amount of enzyme that inhibited the epinephrine formation by 50%.…”
Section: Determination Of Antioxidant Enzyme Activitymentioning
confidence: 99%